Modified Inverse NHE Distribution: Properties and Application - Chaudhary, Arun Kumar; Sapkota, Laxmi Prasad; Kumar, Vijay (Journal of Institute of Science and Technology, 2022)
We have defined a modified form of the inverse NHE distribution in this study. The suggested distribution's hazard function might be shaped like a constant or increasing. Some of the suggested distribution's statistical properties are all clearly derived. Maximum likelihood, Least squares, and Cramer-Von-Mises methods are applied to determine the novel distribution's parameters. For estimators, the asymptotic confidence intervals have been determined as well. The fit of the new distribution is evaluated using an actual data set. We've found that the suggested distribution has proven to be effective in modeling real data set.